On Being and Becoming an Animal: Engelhardt’s Two Notions of Animality - Chorianopoulou, Maria (Conatus - Journal of Philosophy, 2018)
The principal objective of this essay is to briefly present and discuss what could be thought of as Engelhardt’s two approaches on animality. The first, rather literal use of the term, refers to non-rational animals stricto sensu, while the second and more important one thematizes humanity’s ontological self-degradation resulting from the dominant pleasure-oriented culture of our time. As for the first, aiming to moderate his outright acceptance of animal use, I invoke Dworkin’s insights on sanctity, which substantiate a plausible alternative stance. As for the second, I attempt to critically reconstruct the way in which, according to Engelhardt, humanity, having rejected every transcendent inquiry, is increasingly embracing its lower nature. In conclusion, I will hint that this return to animality may be impeded by upcoming challenges that already leave a noticeable imprint on a global scale.